2013
DOI: 10.1007/s13762-013-0214-3
|View full text |Cite
|
Sign up to set email alerts
|

Pollutant association with suspended solids in stormwater in Tijuana, Mexico

Abstract: Stormwater runoff from urban areas is a major source of many pollutants to water bodies. Suspended solids are one of the main pollutants because of their association with other pollutants. The objective of this study was to evaluate the relationship between suspended solids and other pollutants in stormwater runoff in the city of Tijuana. Seven sites were sampled during seven rain events during the 2009-2010 season and the different particle size fractions were separated by sieving and filtration. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 22 publications
1
13
1
Order By: Relevance
“…The size of the particles forming a suspension is very important. Nutrients are usually transported with finer and slower settled fractions (Vaze and Chiew 2004 ; Wakida et al 2014 ). The suspension studies deposited on roads showed similar correlations for heavy metals (Gunawardana et al 2014 ; Zhao et al 2010 ).…”
Section: Research Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the particles forming a suspension is very important. Nutrients are usually transported with finer and slower settled fractions (Vaze and Chiew 2004 ; Wakida et al 2014 ). The suspension studies deposited on roads showed similar correlations for heavy metals (Gunawardana et al 2014 ; Zhao et al 2010 ).…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…One of the most important components of rainwater sewage is a suspension, to which other contaminants are adsorbed, e.g. petroleum compounds or heavy metals (Garbarczyk and Gwoździej-Mazur 2005 ; Gromaire-Mertz et al 1999 ; Sawicka-Siarkiewicz 2003 ; Wakida et al 2014 ). Rainwater run-offs from urban catchments may contain up to 4000 mg dm −3 of suspensions, 6 mg dm −3 of zinc, 0.8 mg dm −3 of copper and 2 mg dm −3 of lead (Królikowski et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing the data obtained from the studies on the performance of vegetative buffer strips in Italy, Borin et al (2010) reported that the young buffer strips can reduce the phosphorous loss up to about 50%, nitrogen loss up to 44% and runoff volume by 33% as compared to the bare areas. Wakida et al (2014) found a high correlation between the concentrations of suspended solids, phosphorus, chemical oxygen demand and turbidity, but not for total nitrogen in the Tijuana city. Campo-Bescos et al (2015) believed that the installation of intense vegetative buffers in irrigated lands can improve the environmental conservation.…”
mentioning
confidence: 78%
“…(Bilotta, Brazier, 2008). They are associated with pollutants such as phosphorus, organic compounds and some heavy metals due to adsorption capacity and can have detrimental effects (Wakida et al, 2014). They are comprised of fine particulate matters suspended in storm runoff that have emanated from natural and anthropogenic sources.…”
Section: Suspended Solidsmentioning
confidence: 99%